Estimation of variance components for lamb weights and fleece yield in Avikalin sheep - Ahmad, Maroof; Singh, C V; Kumar, Sushil (The Indian Journal of Animal Sciences, 2005)
Data recorded on 1313 Avikalin crossbred sheep, spreading over 22 years (1980-2001) were used in present study. Traits analyzed were birth weight (BWT), weaning weight (WWT), 6-months weight (WT6), 12-months weight (WT12) and first greasy fleece yield (GFY1). Additive, phenotypic and environmental covariance between body weights increased with advancing age. The covariances between body weights at different age and first greasy fleece yield also showed similar trends. The h2 estimated under model 2, model 8 and univariate REML animal model were 0.203,0.197 and 0.265, respectively, for BWT; 0.229,0.227 and 0.138, respectively, for WWT; 0.3 12,0.390 and 0.188 for WT6,0.391,0.397 and 0.243, respectively, for WT12 and 0.373, 0.374 and 0.188, respectively, for GFYI. Model 2 and model 8 had higher h2 estimates than univariate REML procedure. The genetic, environmental and phenotypic correlations between all the traits understudy were greater than zero from moderate to high, whereas genetic correlations were slightly higher than phenotypic correlations.